MicroRNA-137-3p Improves Nonalcoholic Fatty Liver Disease through Activating AMPKα. (29th December 2021) - Yu, Yuanjie; He, Chunping; Tan, Shiyun; Huang, Mengjun; Guo, Yitian; Li, Ming; Zhang, Qian
Abstract : Nonalcoholic fatty liver disease (NAFLD) is one of the most common chronic liver diseases worldwide and can develop to nonalcoholic steatohepatitis and later hepatic cirrhosis with a high prevalence to hepatocellular carcinoma. Oxidative stress and chronic hepatic inflammation are implicated in the pathogenesis of NAFLD. MicroRNA-137-3p (miR-137-3p) are associated with oxidative stress and inflammation; however, its role and mechanism in NAFLD remain unclear. Mice were fed with a high-fat diet (HFD) for 24 weeks to establish the NAFLD model. To overexpress or suppress hepatic miR-137-3p expression, mice were intraperitoneally injected with the agomir, antagomir, or respective controls of miR-137-3p at a dose of 100 mg/kg weekly for 6 consecutive weeks before the mice were sacrificed. To validate the involvement of AMP-activated protein kinase alpha (AMPK α ) or cAMP-specific phosphodiesterase 4D (PDE4D), HFD mice were intraperitoneally injected with 20 mg/kg compound C or 0.5 mg/kg rolipram every other day for 8 consecutive weeks before the mice were sacrificed. Hepatic miR-137-3p expression was significantly decreased in mice upon HFD stimulation. miR-137-3p agomir alleviated, while miR-137-3p antagomir facilitated HFD-induced oxidative stress, inflammation, and hepatic dysfunction in mice. Mechanistically, we revealed that miR-137-3p is directly bound to the 3 ′ -untranslated region of PDE4D and subsequently increased hepatic cAMP level and protein kinase A activity, thereby activating the downstream AMPK α pathway. In summary, miR-137-3p improves NAFLD through activating AMPK α and it is a promising therapeutic candidate to treat NAFLD.